The Concept of Emotional Intelligence Islamic Education Perspective in the School Environment - Andika, Nursidik Jaka; Ahmad Muhammad Diponegoro (At-Taqaddum, 2024)
The development of progress in the field of science and technology, especially in terms of communication and information technology, as well as the influence of cultural elements in the era of globalization, has a significant impact on the environment and society. This impact affects people's outlook on life, behavior, values, and even personality. In the current context, education needs to develop individuals who are able to adapt to these advances and become creative and productive human beings. Education in Indonesia is still focused on cognitive aspects and academic values, while important aspects of emotional intelligence are rarely considered. Emotional intelligence is an individual's ability to recognize, understand, manage, and direct their own and others' emotions positively and productively. This research uses qualitative research methods with data analysis through literature studies. The results of this study that emotional intelligence involves managing emotions, self-awareness, motivation, and the ability to manage interpersonal relationships. The concept of emotional intelligence was first introduced by Daniel Goleman. In the context of education, the development of emotional intelligence becomes important in addition to intellectual intelligence. Emotional intelligence can be developed through daily coaching. By examining the concept of emotional intelligence in the perspective of Islamic education, it is hoped that Islamic education can play a role in overcoming educational problems and help develop individual emotional intelligence holistically.